Intracellular delivery of therapeutic antibodies - Hackett, Gavin S. (2012)
Therapeutic antibodies are highly versatile macromolecules that can be engineered to bind and inhibit a target with high specificity. Unfortunately, the cell membrane is impenetrable to antibody reagents, thus limiting their use almost entirely to extracellular targets. Expanding the application of therapeutic antibodies to intracellular targets is an exciting concept that could have a huge impact on how intracellular protein-protein interactions involved in diseases can be modulated. The modification of therapeutic antibodies with Cell Penetrating Peptides (CPPs) can enable cellular penetration, however, no general approach to modifying antibodies with CPPs has been developed that allows for systematic optimisation of both the in vivo and cell penetrating properties.